The species of the genus Thysanarthria d´Orchymont, 1926 (Coleoptera, Hydrophilidae). - Hebauer, Franz (Contributions to Entomology = Beiträge zur Entomologie, 2001)
A short review of the Hydrophilidae genus Thysanarthria d´Orchymont, 1926 is given and 6 species are described as new to science: Thysanarthria bengalensis n. sp., T. brincki n. sp., T. ceylonensis n. sp., T. hongsonensis n. sp., T. madurensis n. sp., T. siamensis n. sp. A short key to all known species is added.KeywordsColeoptera, Hydrophilidae, genus Thysanarthria, review, new species.Nomenclatural Actsbengalensis Hebauer, 2001 (Thysanarthria), spec. n.brincki Hebauer, 2001 (Thysanarthria), spec. n.ceylonensis Hebauer, 2001 (Thysanarthria), spec. n.hongsonensis Hebauer, 2001 (Thysanarthria), spec. n.madurensis Hebauer, 2001 (Thysanarthria), spec. n.siamensis Hebauer, 2001 (Thysanarthria), spec. n.